Liquid level control in a recycle loop. (August 2021) - Kaistha, Nitin
Abstract: A liquid tanks-in-series recycle process is analysed for the effect of the material balance (or inventory) control system (structure and tuning) on dynamics and stability. Two control structures, CS1 and CS2, differing only in the throughput manipulator (TPM) location, are systematically analysed. CS1 has a conventional TPM at the fresh feed flow while CS2 has the TPM at the total (fresh + recycle) flow. Analysis shows that CS2 dynamics can be an order-of-magnitude faster than CS1 for a high recycle fraction ( R ) and a large number of tanks ( N ). PI level control (LC) in CS1 may result in high frequency 'ringing' and potential instability even with conservative individual LC tuning. CS2, on the other hand, is always stable. Furthermore, all control structures with the TPM inside the recycle loop are dynamically agile and stable, similar to CS2. The work clearly illustrates that slow (or even unstable) dynamics in CS1 due to the positive feedback introduced by liquid recycle can be avoided by moving the TPM inside the recycle loop and bringing in the fresh feed as a make-up stream, as in CS2. This is further corroborated through dynamic results for a realistic reactor–separator–recycle process where the plantwide response with the TPM inside the recycle loop is about 5 times faster than a conventional TPM at the fresh feed. Graphical abstract: Highlights: Control structure significantly impacts dynamics of liquid recycle processes. TPM at fresh feed (CS1) and PI level control may result in instability. TPM inside recycle loop (CS2) with PI level control is stable. CS2 dynamically much faster than CS1. Compelling dynamic justification for TPM inside recycle loop.